1984
DOI: 10.1002/j.1460-2075.1984.tb01827.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of platelet membrane glycoproteins and alpha-granule proteins by a human erythroleukemia cell line (HEL).

Abstract: We demonstrate that HEL, a human erythroleukemic cell line, has numerous megakaryocytic markers which were markedly enhanced following the addition of the inducers dimethyl sulfoxide or 12‐O‐tetradecanoylphorbol‐13‐acetate to the culture medium. Ultrastructural and cytochemical studies showed: (i) the presence of organelles morphologically resembling the platelet alpha‐granules; and (ii) a peroxidase activity with the same characteristics as that specifically found in platelets. The platelet alpha‐granule prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
100
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(106 citation statements)
references
References 38 publications
6
100
0
Order By: Relevance
“…It has previously been reported that treatment of HEL cells with phorbol esters induces a dramatic macrophage-like shift in the phenotype of these ceils [11]. This shift has been shown to be associated with the increased expression of several platelet proteins, for example glycoproteins IIb and Illa, platelet factor 4 [6] and more recently the thromboxane A2 receptor [12]. We investigated the regulation of expression of the PGI2 receptor by the phorbol ester, TPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that treatment of HEL cells with phorbol esters induces a dramatic macrophage-like shift in the phenotype of these ceils [11]. This shift has been shown to be associated with the increased expression of several platelet proteins, for example glycoproteins IIb and Illa, platelet factor 4 [6] and more recently the thromboxane A2 receptor [12]. We investigated the regulation of expression of the PGI2 receptor by the phorbol ester, TPA.…”
Section: Discussionmentioning
confidence: 99%
“…However, a human erythroleukemia (HEL) cell line has been established which expresses several megakaryocytic markers of differentiation. It has also been observed that the phorbol ester 12-O-tetradecanoyl-phorbol-13-acetate (TPA) induces the expression of various megakaryocyte/platelet markers in HEL cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Rz effect on 12-LOX was examined in a human erythroleukemia (HEL) cell line that displays platelet-like characteristics. 17 The results demonstrate that the Rz can significantly down-regulate the 12-LOX mRNA and inhibit the enzyme activity by 85%. These results provide (a) a basis for further development of Rz-based gene therapy for cancers and cardiovascular diseases and (b) a tool to study the role of 12-LOX in tumor angiogenesis.…”
mentioning
confidence: 92%
“…HEL is also a cell line derived from a patient with erythroleukemia (Martin and Papayannopoulou, 1982), that coexpresses differentiation markers for both erythroid and megakaryocytic lineages (Martin and Papayannopoulou, 1982;Tabilio et al, 1984;Kieffer et al,1986). HEL cells can undergo further differentiation along various hematopoietic pathways depending on the stimulus (Tabilio et al, 1984;Long et al, 1988Long et al, , 1990.…”
mentioning
confidence: 99%
“…HEL cells can undergo further differentiation along various hematopoietic pathways depending on the stimulus (Tabilio et al, 1984;Long et al, 1988Long et al, , 1990. In recent years, HEL cells have been increasingly used as model system to study molecular aspects of the induction of megakaryocyte differentiation (Hong et al, 1996).…”
mentioning
confidence: 99%